Length changes of Austrian glaciers in 2019/2020 - Lieb, Gerhard Karl; Kellerer-Pirklbauer, Andreas (PANGAEA, 2021)
Glacier length change data of 94 Austrian glaciers were collected for the period summer/autumn 2019 to summer/autumn 2020 (variable period for each glacier depending on specific measurement dates). The measurements in 2020 have been carried out by 19 different teams led by one or two investigators per team. The 94 monitored glaciers are well distributed over the glaciated mountain ranges of the Austrian Alps and consider both small and some of the largest glaciers (up to ca.15 km²) in Austria. Therefore, this sample is considered to be representative for all present-day glaciers in Austria. The monitored glaciers extend from latitude 46°33'N to 47°30'N and longitude 10°04'E to 13°39' E. The data published here comprise the glacier-length-change results for the glaciological year 2019-2020 and are based on a paper published in the official magazine of the Austrian Alpine Club named Bergauf (https://www.alpenverein.at/bk/bergauf/bergauf2021/Bergauf_2_2021/). The collected data are also stored in the database of the World Glacier Monitoring Service (WGMS) in Zurich, Switzerland (https://wgms.ch/). Glacier changes at the 94 glaciers was measured in different ways. First, at 74 glaciers the position of the terminus was quantified for 2019 and 2020 by measuring the distance between distinct marked points in the proglacial area and the ice margin in clearly defined directions (azimuths) for both years. The difference of the measured distances in 2019 and 2020 yields the glacier length change for one specific point. By calculating the arithmetic mean of several of such marked points at a given glacier in 2019/2020, the glacier change value was obtained for glaciers with more than one marked point. Second, at seven Austrian glaciers the position of the glacier terminus was quantified for 2019 and 2020 using Global Navigation Satellite System (GNSS) techniques or other geodetic instruments measuring the glacier terminus for both years. Based on these two GNSS data sets, the glacier length change value was calculated for 2019/2020. Third, for eleven glaciers the change of the glacier position was qualitatively determined by photograph comparison. Results of our analysis show that 85 glaciers retreated, and 7 glaciers remained stationary (i.e., no significant frontal change). For two glaciers it was not possible to quantify glacier change rates for 2019/2020 due to missing data. The mean value of the glacier retreat rate of the 81 glaciers measured in 2018 and 2019 was 15.0 m/a (compared to 14.3 m/a in the previous year). The highest retreat value measured was 104.0 m/a at Hornkees Glacier, Zillertaler Alps. Regarding the wider context, glacier length changes of Austrian Glaciers are measured annually within the framework of a monitoring program of the Austrian Alpine Club. This program is one of the longest glacier monitoring programs and runs since 1891. Measurements of length variations in Austria at single glaciers have been started even earlier dating back to 1878 at Pasterze Glacier. Since that year, glaciological surveys have been carried out almost annually at Pasterze Glacier representing one of the longest time series of continuous glacier monitoring worldwide. For more details regarding the glacier monitoring program of the Austrian Alpine Club visit https://www.alpenverein.at/portal/museum-archiv/gletschermessdienst/index.php (only in German).
Keywords: Alps; Austria; glacier length; glacier monitoring